A randomized controlled trial of a gender‐focused addiction model versus 12‐step facilitation for women veterans. (29th March 2018) - Najavits, Lisa M.; Enggasser, Justin; Brief, Deborah; Federman, Edward
Abstract : Background and Objectives: Substance use disorder (SUD) has increased among women, including military veterans, yet SUD treatment was historically designed for males. This randomized controlled trial compared 12 individual sessions of a gender‐focused SUD recovery model, A Woman's Path to Recovery (WPR) to an evidence‐based, non‐gender‐focused SUD model, 12‐Step Facilitation (TSF) for 66 women veterans with current severe SUD. Methods: The primary outcome was substance use; secondary outcomes were associated problems (e.g., psychological); coping skills, and 12‐step attendance, with assessment at baseline, end‐of‐treatment, and 3‐month followup. Results: Substance use decreased over time, with no difference between conditions. Decreases occurred from baseline to end‐of‐treatment and baseline to followup and, for drug severity, also from end‐of‐treatment to followup. Effect sizes were large for alcohol and medium otherwise. Secondary outcomes were largely consistent with this pattern of improvement. Urinalysis/breathalyzer supported self‐report. Treatment attendance was 62% for WPR and 57% for TSF (not significantly different). Twelve‐step group attendance, surprisingly, did not increase in either condition. Discussion and Conclusions: WPR provides a useful addition to women's SUD treatment options, with outcomes no different than an established evidence‐based model, TSF. Both showed positive impact on substance use and related areas. Our lack of differences based on gender‐focus may reflect women veterans being acculturated to a male military environment. Limitations include lack of an untreated control, a sample limited to veterans, and use of a large effect size for power assumptions. Scientific Significance: This is the first RCT of a gender‐focused approach for women veterans with SUD. (Am J Addict 2018;27:210–216)